THE ROLE, POSITION, AND FUNCTIONS OF VERBAL WITNESSES AS EVIDENCE IN PROVING CRIMINAL CASES ASSOCIATED WITH THE CRIMINAL PROCEDURE CODE (KUHAP) - Tatang Tatang (Fox Justi : Jurnal Ilmu Hukum, 2021)
A criminal case is the act of a person who has violated the provisions of material criminal law, both those stipulated in the Criminal Code (KUHP) and those regulated outside the Criminal Code. The evidence is the central point in the examination of cases in court. This is because through this stage of evidence there is a process, method, act of proving to show whether the defendant is right or wrong in a criminal case in court. However, as time goes by the practice of criminal justice in Indonesia, it is often the case that the testimony of witnesses in front of the trial differs from the information that witnesses give at the investigation stage, which is contained in the minutes of witness examination. If there is a difference in information like this, then the information before the court takes precedence. If the priority is the information in the Witness's BAP, then all of the accusations of the public prosecutor are proven automatically. If something like this happens, then the thing that can be done is to summon the investigating officer who made the BAP to be examined in front of the trial called a verbal witness. The research specification used is descriptive analytical, which provides data or a description as accurately as possible about the object of the problem, while the approach used in this study is a normative juridical approach. The results of this study explain that, The role of verbal witnesses as evidence in proving criminal cases associated with the Criminal Procedure Code (KUHAP) is very important, because it is useful for finding answers regarding the defendant who revoked the Examination Report (BAP) who admitted that he was tortured, forced or he felt trapped by the police during the investigation process, the Judge or the Public Prosecutor presented the Verbalisan Witness to find answers or refutation of what was stated by the defendant..